2023
DOI: 10.3389/fimmu.2023.1145044
|View full text |Cite
|
Sign up to set email alerts
|

Association between the overall burden of comorbidity and Ct values among the older patients with Omicron infection: Mediated by inflammation

Abstract: ObjectivesTo investigate the associations between the overall burden of comorbidity, inflammatory indicators in plasma and Ct values among the elderly with COVID-19.MethodsWe conducted a retrospective observational study. The results of each nucleic acid test of during hospitalization were obtained. Linear regression models assessed the associations between the overall burden of comorbidity, inflammatory indicators in plasma and Ct values among the elderly. A causal mediation analysis was performed to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Although lower Ct values are general understood to infer higher viral loads, an inconclusive relationship between COVID-19 viral loads and disease severity has been described (24). One study demonstrated that the association between disease severity and Ct values depends on COVID-19 cases' overall burden of comorbidities, with disease severity found to be significantly associated with lower Ct values only in cases with a high comorbidity burden (25). Due to a high burden of comorbidities amongst older patients, this would also explain the likelihood of lower Ct values being described amongst older patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although lower Ct values are general understood to infer higher viral loads, an inconclusive relationship between COVID-19 viral loads and disease severity has been described (24). One study demonstrated that the association between disease severity and Ct values depends on COVID-19 cases' overall burden of comorbidities, with disease severity found to be significantly associated with lower Ct values only in cases with a high comorbidity burden (25). Due to a high burden of comorbidities amongst older patients, this would also explain the likelihood of lower Ct values being described amongst older patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of this study showed no significant correlation between nucleic acid CT value fluctuations and age or medical history, which is inconsistent with other related studies ( 39 , 48 , 55 ). Given the weakened immune response and decreased organ reserve capacity in the older adult, leukocyte count and C-reactive protein levels are associated with nucleic acid CT values ( 56 ). Therefore, it is crucial to pay attention to this population to prevent the occurrence of nucleic acid CT value fluctuations, which can cause irreversible damage to the body, aligning with the research on nucleic acid CT value fluctuations in the Northeast region ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, we could not find specific data to corroborate the existence of such subgroups. One study on Omicron infection in the elderly ( Wang et al, 2023 ) associated inflammation and Ct values for upper respiratory viral RNA. Although remaining speculative, therefore, the distinctive subgroups in Fig.…”
Section: Discussionmentioning
confidence: 99%